South Garut Banjarwangi District MSME Product Marketing Strategy - Wida ningsih; Umi Setyorini; Sri Mulyaningsih Kamaru; Heny Herawati (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
This study aims to determine the appropriate and competitive marketing strategy used by MSMEs in the Banjarwangi sub-district. The analysis tool used is SWOT with EFAS/IFAS analysis techniques to determine useful access opportunities for company self-development and IFAS/SAP analysis to determine the strategic advantages possessed by the company. The research was conducted using a survey method in the Banjarwangi sub-district. The SMEs studied were working in the food sector. The results of this study are that the potential strengths and weaknesses of MSMEs in Banjarwangi District are very good to be emulated by MSME actors in any region. The strategy for MSME actors in Banjarwangi District is based on their potential, namely the Growth Strategy (Quadrant I), the marketing strategy of MSMEs in Banjarwangi District. by increasing the number of product variations offered, expanding market share, making prices affordable, providing special discounts on certain purchase quantities, especially for regular customers.